US Municipal Green Bonds and Financial Integration - Guglielmo Maria Caporale; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines mean and volatility spillovers between four green municipal bonds issued by the US states of California, Colorado, Columbia and Ohio, and the role played by the recent Covid-19 pandemic and the COP policy announcements respectively. Specifically, four-variate VAR-GARCH-BEKK models are estimated which include suitably defined dummies corresponding to those events. Significant dynamic linkages (interdependence) between the four municipal bonds under investigation are found in some cases. Moreover, there is evidence of shifts in the second moment parameters coinciding with the Covid-19 pandemic (contagion), whilst the COP policy announcements do not appear to affect the transmission mechanism between municipal green bond returns and volatilities. On the whole, the evidence suggests weaker linkages, and thus a lower degree of financial integration (and greater portfolio diversification opportunities), during the Covid-19 period, though this is likely to be only a temporary phenomenon.
Keywords: C32; G12; G32; 330; municipal bonds; financial integration; spillovers; multivariate GARCH-BEKK; volatility